Hydrothermal method for preparing carbon microspheres by pretreating cellulose at low temperature through alkali / urea aqueous solution
The low-temperature pretreatment of cellulose with an alkali/urea solution followed by hydrothermal reaction addresses the inefficiencies of existing methods, producing stable and cost-effective carbon microspheres for sustainable applications.
Patent Information
- Application Number
- CN202411077921.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Existing methods for preparing carbon microspheres from cellulose are environmentally harmful, costly, and inefficient due to the use of non-renewable resources and high crystallinity of cellulose, which limits its conversion efficiency.
A method involving low-temperature pretreatment of cellulose with an alkali/urea aqueous solution to reduce crystallinity, followed by hydrothermal reaction to synthesize carbon microspheres, using cellulose as a raw material.
This method produces stable, uniform, and environmentally friendly carbon microspheres suitable for large-scale synthesis, with potential applications as catalyst carriers and energy storage materials, while reducing production costs.
Smart Images

Figure CN119118096A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmentally friendly materials, and particularly relates to a method for preparing carbon microspheres by hydrothermal method using cellulose pretreated at low temperature with an alkali / urea aqueous solution. Background Art
[0002] With the rapid growth of the world's population and the rapid development of industry, human demand for energy is increasing day by day, and energy has gradually become an important material basis for economic development and social progress. Since the Industrial Revolution, limited reserves of fossil fuels such as oil, coal and natural gas have been rapidly consumed, causing oil prices to rise, restricting social and economic development, and bringing a series of environmental problems. Under the background of such severe energy pressure and increasingly prominent environmental pollution, it is particularly important to find alternative energy.
[0003] Carbon materials can be applied to lithium-ion batteries, catalyst carriers and other fields due to their good electrical and thermal conductivity. With the discovery of fullerenes and carbon nanotubes, people have paid more attention to carbon materials, especially spherical carbon materials, which stand out from many carbon materials with their excellent performance. Compared with non-renewable resources such as coal-based and asphalt-based raw materials, polymer-based carbon microspheres have attracted a lot of research and attention because their preparation materials are green and renewable and have less environmental pollution.
[0004] At present, the methods commonly used to prepare carbon microspheres in experimental research include template method, arc discharge method and chemical vapor deposition method. The raw materials of these methods mainly come from non-renewable resources such as coal and heavy oil, and their processes are cumbersome, pollute the environment and have high preparation costs. It is precisely based on these shortcomings that researchers are actively looking for new methods for synthesizing carbon microspheres that are more environmentally friendly, energy-saving and sustainable. Among them, the hydrothermal carbonization (HTC) technology with biomass as a precursor continues to gain attention. During the reaction, system pressure is generated by external heating and the saturated vapor pressure of subcritical water. Compared with traditional thermochemical conversion methods, HTC has a low temperature, the raw materials are not limited by moisture content, and it consumes less energy. It has become an efficient biomass pretreatment method and a method for converting all components of biomass.
[0005] Among biomass raw materials, cellulose is a natural polymer with the largest reserves, widest distribution and highest output in the world. The use of cellulose to prepare functional carbon microsphere materials has the characteristics of wide raw material sources, low prices, simple and green preparation process and low production costs. However, cellulose is a polysaccharide-type linear natural polymer with a high degree of polymerization and high crystallinity, which cannot be converted and utilized at a high value. On the one hand, the natural network structure formed by the close entanglement of lignin and hemicellulose with cellulose hinders the conversion efficiency of cellulose; on the other hand, the high crystallinity of cellulose itself also limits the effective conversion of cellulose. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing carbon microspheres by hydrothermal method using cellulose pretreated at low temperature with alkali / urea aqueous solution, which provides broad prospects for large-scale and sustainable synthesis of carbon microspheres and will also open up a new way to synthesize functional carbon materials for the efficient utilization of cellulose.
[0007] The present invention is achieved in that:
[0008] A method for preparing carbon microspheres by hydrothermal method using cellulose pretreated at low temperature with an alkali / urea aqueous solution, which takes cellulose as raw material, adopts an alkali / urea solution to dissolve and pretreat the cellulose at low temperature to obtain a regenerated cellulose gel, then transfers the regenerated cellulose gel to a reactor for hydrothermal reaction, waits for the reactor to cool naturally to room temperature, washes and dries the obtained hydrothermal solid, and obtains carbon microspheres.
[0009] The method specifically comprises the following steps:
[0010] (1) Precooling a mixed solution of sodium hydroxide, urea and distilled water of a certain concentration in a refrigerator at -4°C to -8°C to obtain an alkali / urea solution;
[0011] (2) adding cellulose to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature to completely dissolve the cellulose in the alkali / urea aqueous solution to obtain a transparent cellulose solution;
[0012] (3) precipitating the transparent cellulose solution obtained in step (2) in a dilute acetic acid solution, and then repeatedly washing with distilled water until the solution is neutral, to obtain a cellulose gel solution (neutral);
[0013] (4) centrifuging the cellulose gel solution (neutral) obtained in step (3) to obtain a cellulose gel;
[0014] (5) mixing the cellulose gel obtained in step (4) with distilled water and placing the mixture in a high-temperature reactor for hydrothermal reaction to obtain a hydrothermal carbon mixed solution;
[0015] (6) filtering the hydrothermal carbon mixed solution obtained in step (5), and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres;
[0016] (7) Drying the undried hydrothermal carbon microspheres in step (6) to finally obtain the target product hydrothermal carbon microspheres.
[0017] Further:
[0018] The amount of sodium hydroxide added to the alkali / urea solution in step (1) is 1 to 20%wt.
[0019] The amount of urea added to the alkali / urea solution in step (1) is 1 to 20%wt.
[0020] Preferably, the amount of sodium hydroxide added to the alkali / urea solution in step (1) is 16%, and the amount of urea added is 3%.
[0021] The amount of cellulose added in step (1) is 2% to 6% of the mass of the alkali / urea solution.
[0022] The concentration of the dilute acetic acid in step (3) is 0.1-0.3 mol / L.
[0023] The mass ratio of the cellulose gel to distilled water in step (5) is 1:1 to 2:1.
[0024] The hydrothermal reaction in step (5) is carried out at a hydrothermal temperature of 200 to 280° C. and a heat preservation time of 4 to 8 hours.
[0025] The present invention has the following advantages:
[0026] The present invention obtains cellulose gel by pretreating cellulose with an alkali / urea solution, and directly performs a hydrothermal reaction with the pretreated cellulose hydrogel as a raw material to synthesize hydrothermal carbon microspheres. This method effectively reduces the crystallinity and polymerization degree of cellulose, increases the intensity of the hydrothermal reaction process, and forms more stable, uniform and smooth hydrothermal carbon microspheres. This method provides broad prospects for large-scale and sustainable synthesis of carbon microspheres, which will open up a new way to synthesize functional carbon materials for the efficient utilization of cellulose. The hydrothermal carbon microspheres prepared by this method have the advantages of being environmentally friendly, sustainable and low-cost, and have great potential application value as catalyst carriers, energy storage materials and soft template agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0028] Figure 1 The X-ray diffraction patterns of cellulose raw materials and pretreated cellulose under different alkali / urea solution ratios: (0-5); system 0 (0% NaOH and 0% urea), system 1 (0% NaOH and 19% urea), system 2 (3% NaOH and 16% urea), system 3 (7% NaOH and 12% urea), system 4 (13% NaOH and 6% urea) and system 5 (16% NaOH and 3% urea).
[0029] Figure 2 The hydrothermal carbon paradigm diagram of cellulose raw material and cellulose pretreatment under different alkali / urea solution ratios 。
[0030] Figure 3 For cellulose raw materials and differentHydrothermal carbon microspheres of cellulose pretreated in alkali / urea solution Microstructure Schematic diagram of the structure. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and specific embodiments. If specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0032] Example 1
[0033] (1) placing a mixed solution of 0 g of sodium hydroxide, 19 g of urea and 81 g of distilled water in a refrigerator at -5°C for 10 h to prepare an alkali / urea solution;
[0034] (2) adding 4 g of cellulose (cellulose powder α-cellulose purchased from Inokai) to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature for 5 min to obtain a transparent cellulose solution;
[0035] (3) precipitating the transparent cellulose solution obtained in step (2) in a 0.1 mol / L dilute acetic acid solution, and repeatedly washing with distilled water until the solution becomes neutral, thereby obtaining a cellulose gel solution (neutral);
[0036] (4) centrifuging the cellulose gel solution (neutral) obtained in step (3) at 10,000 rpm for 5 min to obtain a cellulose gel;
[0037] (5) mixing the cellulose gel obtained in step (4) with distilled water in a ratio of 1:1 and placing the mixture in a high-pressure reactor, setting the temperature to 200° C. and the insulation time to 4 h, and obtaining a hydrothermal carbon mixed solution after the reaction is completed;
[0038] (6) filtering the hydrothermal carbon mixed solution obtained in step (5) using a Buchner funnel, and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres;
[0039] (7) Dry the undried hydrothermal carbon microspheres obtained in step (6) in a vacuum drying oven at 105° C. for 4 h to finally obtain the target product, hydrothermal carbon microspheres.
[0040] Example 2
[0041] (1) A mixed solution of 3 g of sodium hydroxide, 16 g of urea and 81 g of distilled water was placed in a refrigerator at -5°C for 10 h to prepare an alkali / urea solution;
[0042] (2) adding 4.5 g of cellulose to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature for 10 min to obtain a transparent cellulose solution;
[0043] (3) precipitating the transparent cellulose solution obtained in step (2) in a 0.15 mol / L dilute acetic acid solution, and repeatedly washing with distilled water until the solution becomes neutral, thereby obtaining a cellulose gel solution (neutral);
[0044] (4) centrifuging the cellulose gel solution (neutral) obtained in step (3) at 10,000 rpm for 15 min to obtain a cellulose gel;
[0045] (5) mixing the cellulose gel obtained in step (4) with distilled water in a ratio of 1.2:1 and placing the mixture in a high-pressure reactor, setting the temperature to 220° C. and the insulation time to 5 h, and obtaining a hydrothermal carbon mixed solution after the reaction is completed;
[0046] (6) filtering the hydrothermal carbon mixed solution obtained in step (5) using a Buchner funnel, and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres;
[0047] (7) Dry the undried hydrothermal carbon microspheres obtained in step (6) in a vacuum drying oven at 105° C. for 4 h to finally obtain the target product, hydrothermal carbon microspheres.
[0048] Example 3
[0049] (1) Place a mixed solution of 7 g of sodium hydroxide, 12 g of urea and 81 g of distilled water in a refrigerator at -5°C for 10 h to prepare an alkali / urea solution;
[0050] (2) adding 4.8 g of cellulose to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature for 15 min to obtain a transparent cellulose solution;
[0051] (3) precipitating the transparent cellulose solution obtained in step (2) in a 0.2 mol / L dilute acetic acid solution, and repeatedly washing with distilled water until the solution becomes neutral, thereby obtaining a cellulose gel solution (neutral);
[0052] (4) centrifuging the cellulose gel solution (neutral) obtained in step (3) at 10,000 rpm for 15 min to obtain a cellulose gel;
[0053] (5) mixing the cellulose gel obtained in step (4) with distilled water in a ratio of 1.5:1 and placing the mixture in a high-pressure reactor, setting the temperature to 240° C. and the insulation time to 6 h, and obtaining a hydrothermal carbon mixed solution after the reaction is completed;
[0054] (6) filtering the hydrothermal carbon mixed solution obtained in step (5) using a Buchner funnel, and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres;
[0055] (7) Dry the undried hydrothermal carbon microspheres obtained in step (6) in a vacuum drying oven at 105° C. for 4 h to finally obtain the target product, hydrothermal carbon microspheres.
[0056] Example 4
[0057] (1) A mixed solution of 13 g of sodium hydroxide, 6 g of urea and 81 g of distilled water was placed in a refrigerator at -5°C for 10 h to prepare an alkali / urea solution;
[0058] (2) adding 5.5 g of cellulose to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature for 20 min to obtain a transparent cellulose solution;
[0059] (3) precipitating the transparent cellulose solution obtained in step (2) in a 0.25 mol / L dilute acetic acid solution, and repeatedly washing with distilled water until the solution becomes neutral, thereby obtaining a cellulose gel solution (neutral);
[0060] (4) centrifuging the cellulose gel solution (neutral) obtained in step (3) at 10,000 rpm for 20 min to obtain a cellulose gel;
[0061] (5) mixing the cellulose gel obtained in step (4) with distilled water in a ratio of 1.8:1 and placing the mixture in a high-pressure reactor, setting the temperature to 260° C. and the insulation time to 6 h, and obtaining a hydrothermal carbon mixed solution after the reaction is completed;
[0062] (6) filtering the hydrothermal carbon mixed solution obtained in step (5) using a Buchner funnel, and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres;
[0063] (7) Dry the undried hydrothermal carbon microspheres obtained in step (6) in a vacuum drying oven at 105° C. for 4 h to finally obtain the target product, hydrothermal carbon microspheres.
[0064] Example 5
[0065] (1) A mixed solution of 16 g of sodium hydroxide, 3 g of urea and 81 g of distilled water was placed in a refrigerator at -5°C for 10 h to prepare an alkali / urea solution;
[0066] (2) adding 6 g of cellulose to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature for 25 min to obtain a transparent cellulose solution;
[0067] (3) precipitating the transparent cellulose solution obtained in step (2) in a 0.3 mol / L dilute acetic acid solution, and repeatedly washing with distilled water until the solution becomes neutral, thereby obtaining a cellulose gel solution (neutral);
[0068] (4) centrifuging the cellulose gel solution (neutral) obtained in step (3) at 10,000 rpm for 25 min to obtain a cellulose gel;
[0069] (5) mixing the cellulose gel obtained in step (4) with distilled water in a ratio of 2:1 and placing the mixture in a high-pressure reactor, setting the temperature to 280° C. and the insulation time to 7 h, and obtaining a hydrothermal carbon mixed solution after the reaction is completed;
[0070] (6) filtering the hydrothermal carbon mixed solution obtained in step (5) using a Buchner funnel, and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres;
[0071] (7) Dry the undried hydrothermal carbon microspheres obtained in step (6) in a vacuum drying oven at 105° C. for 4 h to finally obtain the target product, hydrothermal carbon microspheres.
[0072] Example 6
[0073] The crystallinity of the samples was analyzed by X-ray diffractometer (XRD). Figure 1 The crystallinity of cellulose pretreated with different alkali / urea solution ratios was calculated. The peaks of cellulose without any treatment (system 0) and cellulose treated with only 19% urea (system 1) are basically the same, with the three strongest peaks located at around 14.5°, 16°, and 22.5°, corresponding to the cellulose crystallinity. The 101 and 002 crystal planes are the same as the diffraction pattern of cellulose type I, proving that urea treatment has not changed the crystal form of cellulose. The three strongest peaks of the 2, 3, 4, and 5 systems are located at around 12°, 20°, and 22°, respectively, corresponding to the 101, 002 crystal plane, which is the same as the cellulose II diffraction pattern, proves that after adding sodium hydroxide, the cellulose dissolves and reprecipitates, and the crystal structure changes from crystal I to crystal II. According to the cellulose height method, the crystallinity of cellulose in each system is 78.6%, 75.3%, 62.5%, 51.3%, 46.2% and 42.5%, respectively. The crystallinity of systems 0 and 1 is relatively high, corresponding to cellulose I crystal form. The crystallinity of systems 2, 3, 4 and 5 becomes lower and lower with the increase of sodium hydroxide content. Its crystal form corresponds to cellulose II crystal form, which is in line with the rule that the crystallinity of type II is lower than that of type I. It also proves that after pretreatment with the alkali / urea system, the degree of polymerization of cellulose is reduced and the accessibility of the reaction is improved. Therefore, in the hydrothermal reaction, cellulose pretreated with alkali / urea is more easily hydrolyzed into glucose, and then the glucose begins to dehydrate and polymerize to form aromatic compounds and oligosaccharides; when the solution reaches the critical supersaturation concentration, the oligomers, aromatic compounds and macromolecules containing carboxylic acid groups are further dehydrated to form crystal nuclei. When the pressure and temperature reach a certain level, the crystal nuclei are cross-linked and polymerized to form the final carbon microspheres.
[0074] Example 6
[0075] Energy dispersive spectroscopy (EDS) was used to analyze the elemental composition of the samples. Figure 2 and Table 1). The effect of pretreatment on the hydrothermal carbonization of cellulose under different alkali / urea solution ratios was investigated by elemental analysis. Figure 2 This is a paradigm diagram of hydrothermal carbonization of cellulose after pretreatment with different alkali / urea solution ratios in a high-pressure reactor at 220°C for 5 hours. The reaction type of the hydrothermal carbonization process of cellulose with different alkali / urea solution ratios is qualitatively judged through arrows and directional extensions. The cellulose without any treatment (system 0) is taken as the starting point, and the pretreatment with different alkali / urea solution ratios is taken as the end point of the hydrothermal carbonization sample. The starting point and the end point are connected in sequence, and the main vectors are established in turn. Then, the vector decomposition is performed along the three different arrow directions representing dehydration, decarboxylation and demethylation in the figure. The longer the length of the sub-vector, the more intense the reaction of this type is during the carbonization process. From Figure 2 It can be seen that the reaction type before and after the alkali / urea solution pretreatment has not changed, and the main difference is the intensity of the reaction before and after. Figure 2 It can be seen that the O / C and H / C in the hydrothermal carbon decrease with the increase of the sodium hydroxide ratio. From the direction vector, it can be seen that decarboxylation and dehydroxylation reactions mainly occur.
[0076] Table 1 Hydrothermal carbon microsphere yield and elemental analysis
[0077]
[0078] The cellulose gel obtained by treatment under different alkali / urea solution ratios was hydrothermally synthesized into carbon microspheres, and elemental analysis and yield calculation were performed. Table 1 lists in detail the elemental analysis data of carbon microspheres prepared by hydrothermal method of cellulose treated under different alkali / urea solution ratios. Compared with the control group (system 0), the cellulose treated under different alkali / urea solution ratios: the effect of system 1 treatment shows that its O / C value and H / C value have no obvious changes. When the pretreatment sodium hydroxide ratio is slowly increased, its C element content also shows an increasing trend, while the O / C value and H / C value decrease accordingly. This is because as the degree of cellulose destruction increases, the crystallinity and degree of polymerization decrease significantly, the dehydroxylation and carboxylation reactions are strengthened, resulting in the removal of H and O elements, and the C element content is relatively increased. The changes in the recovery rate of hydrothermal carbon microspheres and the recovery rate of C element during the hydrothermal process were further analyzed. The yield of hydrothermal carbon microspheres prepared from pretreated cellulose compared with raw cellulose decreases with the increase of sodium hydroxide concentration. This is because the increase in sodium hydroxide concentration leads to a decrease in the crystallinity and polymerization degree of cellulose. During the hydrothermal process, most of the accessible cellulose is hydrolyzed into glucose dehydration and polymerization to form aromatic compounds. The aromatic compounds and macromolecules containing carboxylic acid groups are further dehydrated to form crystal nuclei, which are cross-linked and polymerized to form the final carbon microspheres. The yield of hydrothermal carbon microspheres synthesized by glucose is low compared to that of cellulose. This is because many side reactions will occur during the dehydration and polymerization of glucose, while most cellulose is directly aromatized.
[0079] Example 7
[0080] Scanning electron microscopy was used to characterize the samples (see Appendix Figure 3 ). Figure 3 (0) is a hydrothermal carbon microsphere synthesized by hydrothermal reaction of cellulose raw materials; Figure 3 1), 2), 3), 4) and 5) are carbon microspheres synthesized by hydrothermal method from cellulose gel obtained by pretreating cellulose under different alkali / urea solution ratios.
[0081] from Figure 3It can be seen that the carbon microspheres obtained from the cellulose raw materials pretreated by system 1 are basically the same in morphology, because urea has almost no effect on the destruction of cellulose crystallinity, and only plays an auxiliary role in the pretreatment process. The morphology of the hydrothermal carbon microspheres obtained by pretreatment with system 2 is only slightly different from that of system 1, because the content of sodium hydroxide added is small, and the urea ratio accounts for the main part of the solvent, so only a small part of the hydrogen bonds of cellulose are destroyed, and the morphological difference of the carbon microspheres is not obvious. The size distribution of the carbon microspheres in systems 0 to 2 is 2 to 200nm; the hydrothermal carbon microspheres formed are tightly aggregated. Starting from system 3, the particle size of the hydrothermal carbon microspheres has changed significantly, and the size distribution is 1 to 2um; because under low temperature conditions, urea small molecules can prevent cellulose macromolecules from approaching each other, and with the increase of sodium hydroxide content, more and more hydroxide ions can penetrate into the amorphous and crystalline regions of cellulose, resulting in a violent swelling and dissolution effect, thereby destroying the hydrogen bonds between and within cellulose molecules, and strengthening the degree of cellulose hydrolysis during the hydrothermal process. As the ratio of sodium hydroxide is further increased, the particle size of the carbon microspheres of systems 4 and 5 can reach 3 to 20 μm, and the morphology of the hydrothermal carbon microspheres is more uniform and smooth. This is because the alkali / urea solution will destroy the intramolecular and intermolecular hydrogen bonds in the cellulose structure, and the cellulose will be transformed from crystal form I to crystal form II. The degree of crystallinity and degree of polymerization of cellulose will be significantly reduced, in which sodium hydroxide plays a major role. During the hydrothermal reaction, the cellulose with lower crystallinity and degree of polymerization will be more easily hydrolyzed into monosaccharides. Finally, the monosaccharides will undergo dehydration, condensation, polymerization and aromatization to form the final carbon microspheres.
[0082] In summary, the present invention characterizes the change in crystallinity of cellulose under different ratios of alkali / urea aqueous solution and the elemental analysis and morphological structure of hydrothermal carbon microspheres. The dehydration and deoxygenation reactions of cellulose pretreated with different ratios of alkali / urea aqueous solution are enhanced to a certain extent during the hydrothermal process. The scanning electron microscopy results show that the hydrothermal carbon microspheres are uniform, smooth spherical particles with a relatively orderly arrangement, and their particle size increases with the decrease of crystallinity.
[0083] From the X-ray diffraction pattern, it can be seen that the degree of crystallization of cellulose pretreated with alkali / urea is significantly reduced. Elemental analysis shows that cellulose pretreated with alkali / urea aqueous solution undergoes more intense dehydrogenation and deoxygenation reactions during the hydrothermal process than untreated cellulose raw materials, and the hydrothermal carbon microspheres formed are more stable. From the scanning electron microscopy analysis, it can be seen that the hydrothermal carbon microspheres prepared from fibers pretreated with alkali / urea solution are uniform and smooth spherical particles, and the spherical particles are arranged in a relatively orderly manner. Among them, system 5 (16% sodium hydroxide and 3% urea) has the best technical effect: its crystallinity and degree of polymerization are most significantly reduced; in the elemental analysis, the dehydrogenation and deoxygenation reactions are more obvious and more intense, and the hydrothermal carbon microspheres formed are more stable; from the SEM, it can be seen that the morphology of the carbon microspheres is more uniform and smooth.
[0084] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution, characterized in that: Using cellulose as raw material, alkali / urea solution is used to dissolve cellulose under low temperature conditions to obtain regenerated cellulose gel, and then the regenerated cellulose gel is transferred to a reactor for hydrothermal reaction. After the reactor is naturally cooled to room temperature, the obtained hydrothermal solid is washed and dried to obtain carbon microspheres.
2. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 1, characterized in that: The method specifically comprises the following steps: (1) Precooling a mixed solution of sodium hydroxide, urea and distilled water of a certain concentration in a refrigerator at -4°C to -8°C to obtain an alkali / urea solution; (2) adding cellulose to the alkali / urea solution obtained in step (1), and rapidly stirring at room temperature to completely dissolve the cellulose in the alkali / urea aqueous solution to obtain a transparent cellulose solution; (3) precipitating the transparent cellulose solution obtained in step (2) in a dilute acetic acid solution, and then repeatedly washing with distilled water until the solution becomes neutral, thereby obtaining a cellulose gel solution; (4) centrifuging the cellulose gel solution obtained in step (3) to obtain a cellulose gel; (5) mixing the cellulose gel obtained in step (4) with distilled water and placing the mixture in a high-temperature reactor for hydrothermal reaction to obtain a hydrothermal carbon mixed solution; (6) filtering the hydrothermal carbon mixed solution obtained in step (5), and repeatedly washing with ethanol and distilled water until the filtrate becomes clear, thereby obtaining undried hydrothermal carbon microspheres; (7) Drying the undried hydrothermal carbon microspheres in step (6) to finally obtain the target product hydrothermal carbon microspheres.
3. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 2, characterized in that: The amount of sodium hydroxide added to the alkali / urea solution in step (1) is 1 to 20%wt.
4. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 2, characterized in that: The amount of urea added to the alkali / urea solution in step (1) is 1 to 20%wt.
5. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 2, characterized in that: In step (1), the amount of sodium hydroxide added to the alkali / urea solution is 16%, and the amount of urea added is 3%.
6. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 2, characterized in that: The amount of cellulose added in step (1) is 2% to 6% of the mass of the alkali / urea solution.
7. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 2, characterized in that: The mass ratio of the cellulose gel to distilled water in step (5) is 1:1 to 2:
1.
8. The method for preparing carbon microspheres by hydrothermal method of low temperature pretreatment of cellulose with alkali / urea aqueous solution according to claim 2, characterized in that: The hydrothermal reaction in step (5) is carried out at a hydrothermal temperature of 200 to 280° C. and a heat preservation time of 4 to 8 hours.
Citation Information
Patent Citations
Cellulose microsphere as well as preparation method and use thereof
CN101250267A
Preparation method and application of nitrogen-doped starch-based activated carbon microsphere material
CN105948045A
Biological carbon prepared form grapefruit skin, preparation method and application thereof
CN106000303A
Preparation method of bamboo-based cellulose carbon aerogel lithium ion battery anode material
CN111180728A
Preparation method and application of cellulose-based hydrothermal carbon supported aluminum catalyst based on swelling regulation
CN111841521A
Cited By
In-situ self-condensing hydrogel based on hydrothermal carbonization synthesis and preparation method thereof
CN119306885A
Preparation method of super-strong and super-tough hydrogel based on carbon nanomaterial derived from bamboo cellulose
CN120191921A
